In Situ Assembly of Choline Acetyltransferase Ligands by a Hydrothiolation Reaction Reveals Key Determinants for Inhibitor Design. (20th November 2020) - Wiktelius, Daniel; Allgardsson, Anders; Bergström, Tomas; Hoster, Norman; Akfur, Christine; Forsgren, Nina; Lejon, Christian; Hedenström, Mattias; Linusson, Anna; Ekström, Fredrik
Abstract: The potential drug target choline acetyltransferase (ChAT) catalyses the production of the neurotransmitter acetylcholine in cholinergic neurons, T‐cells, and B‐cells. Herein, we show that arylvinylpyridiniums (AVPs), the most widely studied class of ChAT inhibitors, act as substrate in an unusual coenzyme A‐dependent hydrothiolation reaction. This in situ synthesis yields an adduct that is the actual enzyme inhibitor. The adduct is deeply buried in the active site tunnel of ChAT and interactions with a hydrophobic pocket near the choline binding site have major implications for the molecular recognition of inhibitors. Our findings clarify the inhibition mechanism of AVPs, establish a drug modality that exploits a target‐catalysed reaction between exogenous and endogenous precursors, and provide new directions for the development of ChAT inhibitors with improved potency and bioactivity. Abstract : Arylvinylpyridiniums (AVPs), the most widely studied class of inhibitors of the potential drug target choline acetyltransferase (ChAT), act as substrate in an unusual coenzyme A‐dependent hydrothiolation reaction. This in situ synthesis yields an adduct that is the actual enzyme inhibitor. The findings clarify the inhibition mechanism of AVPs and establish a drug modality that exploits a target‐catalyzed reaction between exogenous and endogenous precursors.